Relationship Between Principals’ Plant and School-Community Administrative Skills and Senior Secondary School Teachers’ Job Performance in Adamawa State, Nigeria - Takwate, Kwaji Tizhe; Hamidu, Umaru (Innovare Journal of Education, 2025)
The study investigated the relationship between principals’ plant and school-community administrative skills and senior secondary school teachers’ job performance in Adamawa State, Nigeria. Three research questions and two null hypotheses guided the study using 298 school principals and 6589 teachers as population. A sample of 124 principals and 371 teachers was obtained from three education zones using multi-stage sampling technique. A correlation research design was adopted for the study. The instrument used for data collection in the study was a structured questionnaire titled plant, school-community administrative skills and teachers’ job performance questionnaire (PSCATJPQ). Cronbach Alpha was used to determine the reliability coefficient of the instrument which was found to be .87. Mean scores, standard deviations and Pearson Product Moment Correlation Coefficient were used to answer the research questions and tested the hypotheses. The findings showed that the relationship between principals’ plant, school–community administrative skills and teachers’ job performance were found to be significant in Adamawa State. Based on these findings, the study concluded that principals’ plant and school–community administrative skills relate to teachers’ job performance in Adamawa State. The study recommends among others that government should provide infrastructural facilities to all schools and principals should ensure proper utilization and maintenance and auditing of school plants to provide an enabling environment for teaching and learning. Also, that a functional school-based management committee (SBMC) and parent teachers’ association (PTA) should be set up in all schools to foster effective school-community relationships and better teachers’ job performance.